Effect of gastroprotective agents on upper gastrointestinal bleeding in patients receiving direct oral anticoagulants. (2nd December 2018) - Youn, Sung Hee; Lim, Hyun; Ju, Yeonmi; Soh, Jae Seung; Park, Ji Won; Kang, Ho Suk; Kim, Sung Eun; Moon, Sung Hoon; Kim, Jong Hyeok; Park, Choong Kee; Seo, Seung In; Shin, Woon Geon
Abstract: Objectives: Direct oral anticoagulants (DOACs) are effective in the prevention and treatment of thromboembolism; however, they are associated with upper gastrointestinal bleeding (UGIB). In this study, we evaluated the efficacy of gastroprotective agents (GPAs) in reducing the risk of UGIB in patients receiving DOACs. Methods: We retrospectively reviewed the medical records of 2076 patients who received DOACs for the prevention or treatment of thromboembolic events between January 2008 and July 2016. A cumulative incidence analysis using the Kaplan–Meier method was performed to determine the rate of UGIB and its association with GPAs administration. Results: Of the 2076 patients, 360 received GPAs. Over the follow-up period (1160 person-years), one patient in the GPA group (0.7 per 100 person-years) and 29 patients in the non-GPA group (2.8 per 100 person-years) developed UGIB ( p = .189). In the multivariate analysis, UGIB was associated with older age (hazard ratio (HR), 1.041; p = .048), a history of peptic ulcer or UGIB (HR, 5.931; p < .001), and concomitant use of antiplatelet agents (HR, 3.121; p = .014). GPAs administration did not reduce the risk of UGIB ( p = .289). However, based on the subgroup analysis of 225 patients with concomitant use of antiplatelet agents or a history of peptic ulcer or UGIB, the GPA group (0 per 100 person-years) showed reduced incidence of UGIB compared with the non-GPA group (11.3 per 100 person-years) ( p = .065). Conclusions: The prophylactic use of GPAs could reduce the risk of UGIB in patients receiving DOACs who have risk factors, such as concomitant use of antiplatelet agents or a history of peptic ulcer or UGIB.